Public sector corruption and economic growth in Peru - Bustillos-Gomez, Miler A. (2023)
Objective. To determine the relationship between the perception of public sector corruption and per capita economic growth in Peru, during the period 2000-2018. Methods. The study had a quantitative, correlational approach, developed under a horizontal type of research, derived from the hypothetico-deductive method, based on data from Transparency International, the World Bank and the National Institute of Statistics and Informatics, and made use of a linear model through the ordinary least squares method. Results. The model explains in 30.8% that in the period of analysis, the perception of an increase in GDP per capita is associated with an increase in corruption. Individually, the corruption perception index in the public sector is statistically significant at 5 % so that a one point increase in corruption is associated with an increase in per capita economic growth of 0.45 %. Given that the constant is significant at 5%, there is a 19.9% increase in GDP per capita due to other factors not associated with the study model. Conclusions. It can be determined that the relationship between corruption and economic growth can be complex and multifaceted, because Peru, during the study period, has experienced economic growth with medium levels of corruption.